Concomitant (177)Lu-DOTATATE and capecitabine therapy in malignant paragangliomas - Yadav, Madhav Prasad (EJNMMI Res, 2019)
BACKGROUND: The role of concomitant peptide receptor radionuclide therapy (PRRT) and capecitabine therapy has shown benefit in gastroenteropancreatic neuroendocrine tumors. However, data reporting its role in paraganglioma (PGL) patients is lacking. The aim of this study was to evaluate the role of combined capecitabine and (177)Lu-DOTATATE in malignant PGL patients. METHODS: In this retrospective, single-institutional, single-arm, observational study, data of consecutive advanced stage PGL patients treated with concomitant (177)Lu-DOTATATE-capecitabine therapy, between July 2009 and March 2017, were collected and analyzed. RESULTS: Twenty-five PGL patients received an average dose of 22.86 ± 9.54 (14.43–50) GBq (177)Lu-DOTATATE and 1250 mg/m(2) capecitabine from days 0 to 14, commencing on the morning of PRRT. The median overall survival (OS) was not attained in this patient cohort; however, the median PFS was 32 months. Morphological response according to RECIST 1.1 criteria was achieved in 28% (7/25) patients. Biochemical response with > 50% reduction in chromogranin A levels was observed in 28% of the patients. CONCLUSIONS: Our data confirm that (177)Lu-DOTATATE-capecitabine therapy is effective in achieving an objective response in 28% and symptomatic response in 43% patients. In comparison to published PRRT monotherapy outcomes in PGL, we did not observe any great advantage of concomitant therapy; however, it could be due to under-powered study. We recommend a large randomized trial to prove or disprove the utility of capecitabine as a radiosensitizer for PRRT in PGL patients.